An evolving reservoir neo-fuzzy network for time series prediction - Tyshchenko, O.; Pliss, I. (Видавництво Львівської політехніки, 2014)
Компютінгове сховище – це парадигма навчання періодичних нейронних мереж на основі використання рекуррентної частина (так званого “резервуара”) інших показників. Еволюція систем визначила новий підхід, який фокусується на навчанні нечітких систем, що і мають своїми параметрами їх структуру адаптації он-лайн. У даній роботі розвивається сховище нео-нечітка мережі, побудованої з використанням елементів затримки і нелінійних нео-нечітких синапсів, що означає еволюціонування систем і м’які обчислення об’єднуються в нову обчислювальну систему. Reservoir Computing is a paradigm of training Recurrent Neural Networks based on treating the recurrent part (the so-called “reservoir”) differently from the readouts. This paradigm has become so popular recently due to its computational efficiency and the fact that it’s enough to train only a supervised readout. Meanwhile Evolving Systems define a new approach which focuses on learning fuzzy systems that have both their parameters and their structure adapting on-line. In this paper an evolving reservoir neo-fuzzy network is built using time delay elements and nonlinear neo-fuzzy synapses which means that Reservoir Computing, Evolving Systems and Soft Computing are combined in a new computational system.
Keywords: сховище обчислювальне; еволюціонуюча система; гібридна система; нео-нечіткої нейрон; онлайн процедура навчання; прогнозування; reservoir computing; evolving systems; hybrid systems; neo-fuzzy neuron; online learning procedure; prediction